2015
DOI: 10.4269/ajtmh.14-0613
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Water Treatment Behavior for the Prevention of Cholera in Chad

Abstract: Abstract. Cholera is a well-known and feared disease in developing countries, and is linked to high rates of morbidity and mortality. Contaminated drinking water and the lack of sufficient treatment are two of the key causes of high transmission rates. This article presents a representative health survey performed in Chad to inform future intervention strategies in the prevention and control of cholera. To identify critical psychological factors for behavior change, structured household interviews were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…Regarding the treatment of water, half of the subjects surveyed (50.30%) use the treatment of drinking water while the other half do not treat it. The similar result was found in Chad where 55% of the respondents on behavioral determinants of water treatment in cholera prevention did not use water treatment [20].…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the treatment of water, half of the subjects surveyed (50.30%) use the treatment of drinking water while the other half do not treat it. The similar result was found in Chad where 55% of the respondents on behavioral determinants of water treatment in cholera prevention did not use water treatment [20].…”
Section: Discussionsupporting
confidence: 80%
“…Onjala et al (2014) found that the choice of water treatment was significantly correlated with the quality and risk perception of water [48]. Households select the safest and most reliable source of water for drinking, buy the safest source of water from the market, or practice in-house treatment, and this is triggered by the quality perception, risk to health perception, social norms [49], and the insecurity perception [21]. In our study, the practice of in-house water treatment was significantly reduced after the use of the LCD water as their main source of drinking water at the intervention site, but 65% of households continued to practice treatment.…”
Section: In-house Water Treatment Practice and Costmentioning
confidence: 99%
“…The most important factors for the promotion of drinking water chlorination were risk perceptions, social norms, and self-efficacy convictions, which differed significantly between survey participants who were performing water treatment and those who were not at the time of survey (details can be found in [23]). …”
Section: Introductionmentioning
confidence: 99%
“…We examine which behavioral factors play an important role in maintaining behavior by utilizing the baseline data from [23]. To observe what changes in psychosocial factors occurred over time in different user groups, a second survey was conducted in the same study sample.…”
Section: Introductionmentioning
confidence: 99%